Hypoplastic Left Heart Syndrome – Unresolved Issues - Arnold, Raoul Roman; Loukanov, Tsvetomir; Gorenflo, Matthias (Frontiers in Pediatrics, 2014)
Hypoplastic left heart syndrome (HLHS) is one of the most challenging congenital heart defects. At present, it is expected that – at best – 70% of newborns with HLHS will reach adulthood. This review addresses the problems of right ventricular (RV) failure and insufficient growth of pulmonary vasculature in these patients. In order to further improve long-term prognosis translational research to control RV function, growth of pulmonary arteries and progress in chronic circulatory support are clearly needed to provide a further improvement for adults with HLHS.